Lusophone interfaces: the lusophone network on Facebook - Amaral, Inês (2016)
This article examines the new digital landscape postulated in the network society theory advocated by Castells (2000), as well as a contextual framework. Assuming the virtual exists and produces effects (Lévy, 2001), we consider that we are witnessing a change of paradigm in social communication. If from a Communication point of view we are facing individualisation, the social paradigm shift is evident. The new perspective inculcated by digital tools is the socialisation and the maximisation of the collective. In this article, we assume that the relational ties in asymmetric social networks (which do not involve reciprocity between nodes) that take place in social media platforms is content. In this sense, and taking a multidisciplinary perspective, we consider that the technique of appropriation shows a mapping of structures that are technically mediated interactions and enhanced by technology. We present an empirical study based on the method of triangulation, crossing document analysis with netnography. Analysing groups and Facebook pages as supports, where communication is recontextualised through disaggregated distribution and different types of interaction, we aim to categorise and understand the social representations of the Lusophone. The main objective of this paper is to examine whether Facebook, as an area of digitally mediated interactions and disaggregate content sharing, can induce a reconstruction of the significance of social networks and representations of the Lusophone, promoting the creation of a single social group, or at least a grouping with some homogeneity.